Study On Time Efficiency of Unloading Time of The Purse Seiner at Fishing Port of PT. Hasil Laut Sejati, Riau Islands Province - Alfin '; Jonny Zain; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on Agustus 2013 at the fishing port of PT. Hasil Laut Sejati, Batam city Riau Islands Province. The method used was a survey method. The purpose of this study is to know the efficiency level for unloading time of purse seiner in fishing port of PT. Hasil Laut Sejati and factor influenced. The result shows that the efficiency level of unloading time around 56,98% - 72,73% with uploading efficiency time was 64,65% in average. There are seven free variables influence time efficiency for unloading time with value r=0,897 and R2=89,7%, thus the diversity of free variable gives the contribution to diversity assess for time efficiency is equal 89,7%.Keyword : Efficiency, fishing port, purse seine, unloading time